Mentoring community pharmaceutical technicians incubator to reduce high-alert drugs pre-dispensing errors and promote functional competency - Teeraporn Saeheaw (2019)
© 2019 Inderscience Enterprises Ltd. Unstructured training program caused new pharmaceutical technicians' misinformation in pre-dispensing operation which reflected in increasing pre-dispensing error rates, and their poor functional competency. To improve hospital accreditation quality, this paper presents a learning innovation 'mentoring community pharmaceutical technicians incubator' by integrating: 1) mentoring CoPs as an incubator to bring up conceptual knowledge and new experience layers; 2) CommonKADs 'knowledge model' as a knowledge acquisition method; 3) common functional competency standard as competency measurement criteria. Results showed that the incubator reduced drugs and high-alert drugs pre-dispensing errors into hospital standard. Functional competency in week 1-5 improved 1.18 scores (29.5%), and week 6-10 was at 0.50 scores (12.5%). Knowledge model illustrated that two inference layers were created, and domain knowledge was growing more than 50%. This paper suggests that the proposed incubator can promote Thai new pharmaceutical technicians in knowledge, competence, and performance layers by shifting from unstructured training program to reach higher levels of learning.